Synthesis of Acridones by Palladium-Catalyzed Buchwald–Hartwig Amination - Janke, Julia; Villinger, Alexander; Ehlers, Peter; Langer, Peter (Synlett, 2019)
The Buchwald–Hartwig amination allows an efficient and convenient synthesis of biologically and pharmaceutically important acridones by formation of a six-membered ring. With the described method, a number of derivatives have been synthesized in up to 95% yield by using a variety of anilines as well as benzylic and aliphatic amines.
Keywords: palladium catalysis; Suzuki–Miyaura reaction; Buchwald–Hartwig amination; acridones; cyclization